1995
DOI: 10.1038/376253a0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of posterior gap gene expression in the Drosophila blastoderm

Abstract: The process of body prepatterning during Drosophila blastoderm formation relies on the localized activities of zygotic segmentation genes, which are controlled by asymmetrically distributed maternal determinants. The anterior determinant bicoid, a homeodomain transcription factor, forms an anterior-to-posterior concentration gradient. It interacts with the maternal transcription factor hunchback to activate the anterior zygotic patterning genes, including the central gap gene Krüppel (Kr). In contrast, the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
190
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(199 citation statements)
references
References 27 publications
9
190
0
Order By: Relevance
“…To determine whether dCBP may participate in enhancerspecific activities of Bcd, we took advantage of another reporter gene, kni-CAT, which contains the 64-bp Bcd-responsive kni enhancer element (17). Our co-transfection experiments showed that, whereas dCBP increased the activity of Bcd on hb-CAT reporter by 19 fold (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether dCBP may participate in enhancerspecific activities of Bcd, we took advantage of another reporter gene, kni-CAT, which contains the 64-bp Bcd-responsive kni enhancer element (17). Our co-transfection experiments showed that, whereas dCBP increased the activity of Bcd on hb-CAT reporter by 19 fold (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite its critical biological role and extensive previous studies, it remains unclear how Bcd activates transcription and what other factors participate in the activation process (15,16). Another important issue on Bcd as a molecular morphogen relates to its special ability to activate different target genes in distinctive manners (13,(17)(18)(19). Only recent studies have begun to shed light on this important issue, suggesting that enhancer architecture can influence how Bcd binds DNA and activates transcription (20).…”
mentioning
confidence: 99%
“…1). Possibly, Ma-bcd is repressing translation of a Megaselia caudal homolog more posteriorly than in the Drosophila embryo (50,51) and/or Ma-bcd has a stronger inf luence on the activation of posterior gap genes such as Krüppel and knirps (7,52). However, the additional requirement for bicoid might not be linked to increased hunchback function in the more primitive f ly species, because the relevant expression of this gene is conserved (Fig.…”
Section: Ma-bcd Rnai Causes Symmetrical Double Abdomen In Megaseliamentioning
confidence: 99%
“…The head and thorax are replaced by duplicated posterior terminal structures of reversed polarity (4). The morphogen-like function of Bicoid requires cooperation with the zinc finger type transcription factor Hunchback in determining the anterior segment pattern; posteriorly, Bicoid complements the homeodomain transcription factor caudal in a partially redundant manner (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Several CRMs (including kni and hairy 7) also contain clusters of binding sites for Caudal (Cad), which is expressed in a posterior gradient (38). Previous work suggests that Cad functions with Bcd to activate expression of these CRMs (39,40).…”
Section: Ap Positioning By Combinations Of Activators Andmentioning
confidence: 99%